Perkawinan Katolik dalam Sistem Hukum Ganda di Indonesia: Hukum Positif dan Hukum Gereja - Fidelis Harefa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
Catholic marriage in Indonesia occupies a unique legal position because it is governed simultaneously by state law and canon law. Indonesian positive law recognizes marriage based on religious law and regulates its civil consequences, including divorce. However, Catholic canon law does not recognize divorce as the dissolution a valid and sacramental marriage. This dual legal framework has led widespread misunderstandings among Catholic faithful and legal practitioners, particularly regarding the legal consequences of civil divorce. This study aims to analyze the legal status of Catholic marriage within Indonesia’s dual legal system and examine the juridical implications of civil divorce Catholic marital status under canon law. This research employs normative legal research using statutory, conceptual, and comparative normative approaches. The findings demonstrate that civil divorce functions solely as the termination of civil legal relations under state law and does not dissolve the marital bond according to canon law. The study further reveals that prevailing misconceptions stem from reductive understanding Catholic marriage merely an administrative legal event. This article contributes to legal scholarship by clarifying the normative boundaries between state law and canon law and emphasizes the need for comprehensive legal understanding to prevent recurring juridical misunderstandings in Catholic marriage practices in Indonesia.